Statistics (based on CMO 03 series 2007) - Arao, Rosalia R.; CoPo, Antonio Roland I. ;Arce, Ma. Teresa B.;Laddaran, Angeline T. ;Mejia, Leila D. ;Gabuyo, Yonardo A. (Quezon City, Philippines : Rex Book Store, 2010)
It aims to provide students with fundamental understanding of concepts of different theories, principles and methods in statistics including statistical inferences necessary to effectively employ its application in real life most especially in contemporary business situations.
Chapter 1. Review of the basic Mathematical Operations with Implications for Accounting -- Chapter 2. Principles of Counting and Theories of Probability -- Chapter 3. Types of Probability distribution -- Chapter 4. Sampling and Sampling distribution -- Chapter 5. Statistical Estimation -- Chapter 6. Introduction to Hypothesis testing -- Chapter 7. Simple regression -- Chapter 8. Statistical Presentation as an Aid to Reporting Information -- Chapter 9. The use of computer to generate statistical presentations of data and showing these presentations.
Includes bibliographical references.
Keywords: STATISTICS